Dinamika Konstruksi Nilai Kelompok Pelajar Sekolah Menengah Atas Yogyakarta (Studi Fenomenologis Konstruksi Nilai Kelompok Pada GNB di SMA Negeri 6 Yogyakarta) - , DYARA RADIANING ANGGITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The phenomenon of student gang in Yogyakarta in the past time was often discussed as the deviation and violence. It is quite interesting when we discuss how this phenomenon comes from students, especially school which is believed as the institution to educate people. From this opportunity, researcher would like to look over specifically how these high school students who get involved in gang activities construct the values to themselves. One of the famous gang with high violence act is GNB, a student gang from 6 Senior High School Yogyakarta. GNB is well known as many meaning like Gerakan Non Bodjo, Gerakan Non Blok, and Guyub Ngisor Beringin. The group existed since 1995 and ended in 2010 by the former students before. This research is aimed to be the reflection in education institution to see student gang cases from different perspective. So that to avoid violence and crime in school can use the preventive way and based on the condition in the field. The method that is used here is phenomenology. Phenomenology is aimed to see further about what is inside the reality so what is seen and understood not only the visible thing. By this method, researcher can also get involved and learn the world of other people who has the different construction and life experience without doing intervention whether it is the wrong or the right thing. As a special case, this research used trancendental phenomenology that focused on the experience of the people as the main object and minimize the interpretation from the researcher herself. Besides, this research also combines the historical method as one of the way in searching for the journey from the beginning to the ending of the group. The result of this research shows that there is the dynamics in constructing group values, so that every member has the different perception year by year. Furthermore, when fighting (tawuran) becomes the main concept as the collective strength of GNB. It means that in understanding GNB from the perspective of identity, values, and function, every year the student has different understanding. Although, at the end heterogenity through one main line, solidarity. The existence of GNB in the school area, 6 Senior High School, has the impact to the studentâs activities in the organizations. For example, when the election of the OSIS leader is held. They usually provoke to do some hidden campaign ensuring that every student vote the people they (GNB) choose. This has been the strategy for GNB to get involved in formal organizationâs activities. They expect to control the rules and decision that are made by the school so the studentâs needs can be fulfilled better